Pre-Operative Plasma Extracellular Vesicle Proteins are Associated with a High Risk of Long Term Secondary Major Cardiovascular Events in Patients Undergoing Carotid Endarterectomy. (November 2021) - Timmerman, Nathalie; Waissi, Farahnaz; Dekker, Mirthe; van de Pol, Qiu Ying; van Bennekom, Joelle; Schoneveld, Arjan; klein Avink, Marjet J.M.; de Winter, Robbert J.; Pasterkamp, Gerard; de Borst, Gert J.; de Kleijn, Dominique P.V.
Abstract : Objective: Patients undergoing carotid endarterectomy (CEA) maintain a substantial residual risk of major cardiovascular events (MACE). Improved risk stratification is warranted to select high risk patients qualifying for secondary add on therapy. Plasma extracellular vesicles (EVs) are involved in atherothrombotic processes and their content has been related to the presence and recurrence of cardiovascular events. The association between pre-operative levels of five cardiovascular disease related proteins in plasma EVs and the post-operative risk of MACE was assessed. Methods: In 864 patients undergoing CEA from 2002 to 2016 included in the Athero-Express biobank, three plasma EV subfractions (low density lipoprotein [LDL], high density lipoprotein [HDL], and tiny extracellular vesicles [TEX]) were isolated from pre-operative blood samples. Using an electrochemiluminescence immunoassay, five proteins were quantified in each EV subfraction: cystatin C, serpin C1, serpin G1, serpin F2, and CD14. The association between EV protein levels and the three year post-operative risk of MACE (any stroke, myocardial infarction, or cardiovascular death) was evaluated using multivariable Cox proportional hazard regression analyses. Results: During a median follow up of three years (interquartile range 2.2 – 3.0), 137 (16%) patients developed MACE. In the HDL-EV subfraction, increased levels of CD14, cystatin C, serpin F2, and serpin C1 were associated with an increased risk of MACE (adjusted hazard ratios per one standard deviation increase of 1.30, 95% confidence interval [CI] 1.15–1.48; 1.22, 95% CI 1.06–1.42; 1.36, 95% CI 1.16–1.61; and 1.29, 95% CI 1.10–1.51; respectively), independently of cardiovascular risk factors. No significant associations were found for serpin G1. CD14 improved the predictive value of the clinical model encompassing cardiovascular risk factors (net re-classification index = 0.16, 95% CI 0.08–0.21). Conclusion: EV derived pre-operative plasma levels of cystatin C, serpin C1, CD14, and serpin F2 were independently associated with an increased long term risk of MACE after CEA and are thus markers for residual cardiovascular risk. EV derived CD14 levels could improve the identification of high risk patients who may benefit from secondary preventive add on therapy in order to reduce future risk of MACE.